(3aGFOI HgGFjI Ydi JaSjQ GdHjVGhis - (3GdHgGFis; (3YHO Gddg Hf YeQ Hf eMeO Hf Ydj , GdTjQGRj GdHjVGhj, CHh SYjO CHh GdNjQ fGUQ GdOjf,J (B685 (3g` s ((3edc MSjf Hf edc s)
(3ChdgG (B:s
(3bGd Gdgd SHMGfI ai ShQI Gdedc (B:" (3cdeG Cdbi ajgG ahL SCdge NRfJgG Cde jCJce fPjQ(B" (3abGd GdaGVd GdHjVGhi HYO gPg GdBjI aCSMbge Gddg SMbkG s
(3BNQgG (B:s
(3dh bGd aSMbkG dge hdCUMGH GdSYjQ de jcf ai GdcdGe NWQ HGdNGWQ GdaGFR hGddg CYde HMbjbI GdMGd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HBNQgG fbhd eNJdaIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B110 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B298s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs